Impact of warmer winters on the flowering display of Tokyo cherry (Cerasus ×yedoensis ‘Somei-yoshino’) at its southern range - Toshio Katsuki; Seiichi Kanetani; Yuki Kedoin; Takumi Fujiwara; Hiroyuki Iketani; Abraham J. Miller-Rushing; Richard B. Primack (International Journal of Biometeorology, 2026)

Local soil temperature advances flowering phenology of Canada mayflower (Maianthemum canadense), with implications for climate change assessment - Richard B. Primack; Selby Vaughn; Carina Terry (Oecologia, 2025)

Honey bees and native flower visitors in a Boston suburb: Assessing coexistence and conservation strategies - Katia Tiana Landauer; Selby Vaughn; Richard B. Primack (Biological Conservation, 2024)

Big scientific conferences return and emphasize the human context of science - Abraham J. Miller-Rushing; Richard B. Primack; Eric D. Nana (Biological Conservation, 2024)

Spatial variability in herbaceous plant phenology is mostly explained by variability in temperature but also by photoperiod and functional traits - Robert Rauschkolb; Solveig Franziska Bucher; Isabell Hensen; Antje Ahrends; Eduardo Fernández-Pascual; Katja Heubach; Desiree Jakubka; Borja Jiménez-Alfaro; Andreas König; Tomáš Koubek; Alexandra Kehl; Anzar A. Khuroo; et al. (International Journal of Biometeorology, 2024)
Whereas temporal variability of plant phenology in response to climate change has already been well studied, the spatial variability of phenology is not well understood. Given that phenological shifts may affect biotic interactions, there is a need to investigate how the variability in environmental factors relates to the spatial variability in herbaceous species’ phenology by at the same time considering their functional traits to predict their general and species-specific responses to future climate change. In this project, we analysed phenology records of 148 herbaceous species, which were observed for a single year by the PhenObs network in 15 botanical gardens. For each species, we characterised the spatial variability in six different phenological stages across gardens. We used boosted regression trees to link these variabilities in phenology to the variability in environmental parameters (temperature, latitude and local habitat conditions) as well as species traits (seed mass, vegetative height, specific leaf area and temporal niche) hypothesised to be related to phenology variability. We found that spatial variability in the phenology of herbaceous species was mainly driven by the variability in temperature but also photoperiod was an important driving factor for some phenological stages. In addition, we found that early-flowering and less competitive species characterised by small specific leaf area and vegetative height were more variable in their phenology. Our findings contribute to the field of phenology by showing that besides temperature, photoperiod and functional traits are important to be included when spatial variability of herbaceous species is investigated.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

Wildlife rehabilitation records reveal impacts of anthropogenic activities on wildlife health - Tara K. Miller; Karra Pierce; Edward E. Clark; Richard B. Primack (Biological Conservation, 2023)

Ten best practices for effective phenological research - Richard B. Primack; Amanda S. Gallinat; Elizabeth R. Ellwood; Theresa M. Crimmins; Mark D. Schwartz; Michelle D. Staudinger; Abraham J. Miller-Rushing (International Journal of Biometeorology, 2023)
The number and diversity of phenological studies has increased rapidly in recent years. Innovative experiments, field studies, citizen science projects, and analyses of newly available historical data are contributing insights that advance our understanding of ecological and evolutionary responses to the environment, particularly climate change. However, many phenological data sets have peculiarities that are not immediately obvious and can lead to mistakes in analyses and interpretation of results. This paper aims to help researchers, especially those new to the field of phenology, understand challenges and practices that are crucial for effective studies. For example, researchers may fail to account for sampling biases in phenological data, struggle to choose or design a volunteer data collection strategy that adequately fits their project’s needs, or combine data sets in inappropriate ways. We describe ten best practices for designing studies of plant and animal phenology, evaluating data quality, and analyzing data. Practices include accounting for common biases in data, using effective citizen or community science methods, and employing appropriate data when investigating phenological mismatches. We present these best practices to help researchers entering the field take full advantage of the wealth of available data and approaches to advance our understanding of phenology and its implications for ecology.

Grass flowering times determined using herbarium specimens for modeling grass pollen under a warming climate - Natalie Iwanycki Ahlstrand; Hannah M. Elvery; Richard B. Primack (Science of The Total Environment, 2023)

Disorder or a new order: How climate change affects phenological variability - Michael Stemkovski; James R. Bell; Elizabeth R. Ellwood; Brian D. Inouye; Hiromi Kobori; Sang Don Lee; Trevor Lloyd‐Evans; Richard B. Primack; Barbara Templ; William D. Pearse (Ecology, 2023)
Advancing spring phenology is a well documented consequence of anthropogenic climate change, but it is not well understood how climate change will affect the variability of phenology year to year. Species' phenological timings reflect the adaptation to a broad suite of abiotic needs (e.g., thermal energy) and biotic interactions (e.g., predation and pollination), and changes in patterns of variability may disrupt those adaptations and interactions. Here, we present a geographically and taxonomically broad analysis of phenological shifts, temperature sensitivity, and changes in interannual variability encompassing nearly 10,000 long‐term phenology time series representing more than 1000 species across much of the Northern Hemisphere. We show that the timings of leaf‐out, flowering, insect first‐occurrence, and bird arrival were the most sensitive to temperature variation and have advanced at the fastest pace for early‐season species in colder and less seasonal regions. We did not find evidence for changing variability in warmer years in any phenophase groups, although leaf‐out and flower phenology have become moderately but significantly less variable over time. Our findings suggest that climate change has not to this point fundamentally altered the patterns of interannual phenological variability.

Correction to: A comparison of herbarium and citizen science phenology datasets for detecting response of flowering time to climate change in Denmark - Natalie Iwanycki Ahlstrand; Richard B. Primack; Anders P. Tøttrup (International Journal of Biometeorology, 2022)

A comparison of herbarium and citizen science phenology datasets for detecting response of flowering time to climate change in Denmark - Natalie Iwanycki Ahlstrand; Richard B. Primack; Anders P. Tøttrup (International Journal of Biometeorology, 2022)
Phenology has emerged as a key metric to measure how species respond to changes in climate. Innovative means have been developed to extend the temporal and spatial range of phenological data by obtaining data from herbarium specimens, citizen science programs, and biodiversity data repositories. These different data types have seldom been compared for their effectiveness in detecting environmental impacts on phenology. To address this, we compare three separate phenology datasets from Denmark: (i) herbarium specimen data spanning 145 years, (ii) data collected from a citizen science phenology program over a single year observing first flowering, and (iii) data derived from incidental biodiversity observations in iNaturalist over a single year. Each dataset includes flowering day of year observed for three common spring-flowering plant species: Allium ursinum (ramsons), Aesculus hippocastanum (horse chestnut), and Sambucus nigra (black elderberry). The incidental iNaturalist dataset provided the most extensive geographic coverage across Denmark and the largest sample size and recorded peak flowering in a way comparable to herbarium specimens. The directed citizen science dataset recorded much earlier flowering dates because the program objective was to report the first flowering, and so was less compared to the other two datasets. Herbarium data demonstrated the strongest effect of spring temperature on flowering in Denmark, possibly because it was the only dataset measuring temporal variation in phenology, while the other datasets measured spatial variation. Herbarium data predicted the mean flowering day of year recorded in our iNaturalist dataset for all three species. Combining herbarium data with iNaturalist data provides an even more effective method for detecting climatic effects on phenology. Phenology observations from directed and incidental citizen science initiatives will increase in value for climate change research in the coming years with the addition of data capturing the inter-annual variation in phenology.

Plant and bird phenology and plant occurrence from 1851 to 2020 (non‐continuous) in Thoreau's Concord, Massachusetts - Elizabeth R. Ellwood; Amanda S. Gallinat; Caitlin McDonough MacKenzie; Tara Miller; Abraham J. Miller‐Rushing; Caroline Polgar; Richard B. Primack (Ecology, 2022)
Concord, Massachusetts, USA has served as an active location for phenological observations since philosopher and naturalist Henry David Thoreau began recording plant and animal occurrence and phenology in 1851. Since that time, numerous naturalists, scientists, and researchers have continued this tradition, creating an invaluable time series of 758 species in a single location. In total, 13,441 phenological records, spanning 118 years, now exist, with observations of many species ongoing. Relative abundance data for an additional 200 plant species is also provided. Thoreau's published journals and records in Special Collections libraries at the Concord Free Public Library, Harvard University, Peabody Essex Museum, and Morgan Library and Museum provide insight into his methods of routinely walking around Walden Pond, through natural areas, and within the town of Concord, seeking the first leaf or flower on plants, seasonal observations of migratory birds, and fruit maturation times. Several amateur naturalists, and most recently the present research group, have followed this method of regularly searching Concord for the earliest signs of seasonal events, visiting many of the same locations including Walden Pond, the site made famous by Thoreau. While Thoreau's observations were initially made out of a curious desire to document the natural world, these data have led to dozens to contemporary studies, addressing timely issues such as climate change, conservation, ecology, and invasive species. This time series of data, initiated by Thoreau and continued by others, has resulted in dozens of peer‐reviewed publications, a popular science book, and numerous educational and outreach opportunities. These data grow increasingly valuable with time and as new and creative studies are undertaken with Thoreau's historic records. No copyright restrictions apply to the use of this data set other than citing this publication.

Siberian plants shift their phenology in response to climate change - Sergey Rosbakh; Florian Hartig; Denis V. Sandanov; Evgenya V. Bukharova; Tara K. Miller; Richard B. Primack (Global Change Biology, 2021)
Siberia has undergone dramatic climatic changes due to global warming in recent decades. Yet, the ecological responses to these climatic changes are still poorly understood due to a lack of data. Here, we use a unique data set from the Russian ‘Chronicles of Nature’ network to analyse the long‐term (1976–2018) phenological shifts in leaf out, flowering, fruiting and senescence of 67 common Siberian plant species. We find that Siberian boreal forest plants advanced their early season (leaf out and flowering) and mid‐season (fruiting) phenology by −2.2, −0.7 and −1.6 days/decade, and delayed the onset of senescence by 1.6 days/decade during this period. These mean values, however, are subject to substantial intraspecific variability, which is partly explained by the plants' growth forms. Trees and shrubs advanced leaf out and flowering (−3.1 and −3.3. days/decade) faster than herbs (−1 day/decade), presumably due to the more direct exposure of leaf and flower buds to ambient air for the woody vegetation. For senescence, we detected a reverse pattern: stronger delays in herbs (2.1 days/decade) than in woody plants (1.0–1.2 days/decade), presumably due to the stronger effects of autumn frosts on the leaves of herbs. Interestingly, the timing of fruiting in all four growth forms advanced at similar paces, from 1.4 days/decade in shrubs to 1.7 days/decade in trees and herbs. Our findings point to a strong, yet heterogeneous, response of Siberian plant phenology to recent global warming. Furthermore, the results highlight that species‐ and growth form‐specific differences among study species could be used to identify plants particularly at risk of decline due to their low adaptive capacity or a loss of synchronization with important interaction partners.

Macro‐scale variation and environmental predictors of flowering and fruiting phenology in the Chinese angiosperm flora - Yanjun Du; Lingfeng Mao; Simon A. Queenborough; Richard Primack; Liza S. Comita; Arndt Hampe; Keping Ma (Journal of Biogeography, 2020)
Aim The timing of reproduction is a major determinant of the geographical distribution of plant species and resulting patterns of community assembly, yet few studies have assessed how the reproductive phenology of plant assemblages varies across large geographical and environmental gradients. In addition, it remains poorly known to what extent phenological trends and their drivers differ between flowering and fruiting phases or among different growth forms. To address these knowledge gaps, we examined the reproductive phenology and potential climatic drivers in herbaceous and woody species in ecosystems across China that varied in climate (temperate to tropical) seasonality and elevation. Location China. Methods We used data from the Flora Republicae Popularis Sinicae to estimate angiosperm flowering ( n = 16,717 species) and fruiting ( n = 11,605) phenology for 100 x 100 km grid cells ( n = 943) throughout China. We assessed large‐scale geographical trends in mean flowering and fruiting date and the time needed for fruit development. The relationships of these phenological variables with seven climate variables were examined using both ordinary and spatial linear regression. Results Higher latitudes and elevations had considerably reduced length of the reproductive season, with later flowering and earlier fruiting than lower latitudes and elevations. Woody plant assemblages flowered markedly earlier and needed three times longer for fruit development, and tended to show steeper geographical trends in reproductive phenology than herbaceous assemblages. Herbs and woody species differed strongly in their climatic triggers of flowering but largely shared the same cues for fruiting. Main conclusions Woody species compensate for longer seed development times by an earlier onset of flowering, yet reproduction in both life‐forms has stronger climatic constraints. Distinct climatic drivers suggest that herbaceous and woody species assemblages will respond differently to climate change. Overall, our findings underpin the role of reproductive phenology as a key biological mechanism through which climate shapes large‐scale geographical trends in species richness, phylogenetic diversity and community assembly.

Leaf longevity in temperate evergreen species is related to phylogeny and leaf size - Linnea Smith; Richard B. Primack; Lucy Zipf; Sarah Pardo; Amanda S. Gallinat; Zoe A. Panchen (Oecologia, 2019)

Phenological mismatch with trees reduces wildflower carbon budgets - J. Mason Heberling; Caitlin McDonough MacKenzie; Jason D. Fridley; Susan Kalisz; Richard B. Primack (Ecology Letters, 2019)
Interacting species can respond differently to climate change, causing unexpected consequences. Many understorey wildflowers in deciduous forests leaf out and flower in the spring when light availability is the highest before overstorey canopy closure. Therefore, different phenological responses by understorey and overstorey species to increased spring temperature could have significant ecological implications. Pairing contemporary data with historical observations initiated by Henry David Thoreau (1850s), we found that overstorey tree leaf out is more responsive to increased spring temperature than understorey wildflower phenology, resulting in shorter periods of high light in the understorey before wildflowers are shaded by tree canopies. Because of this overstorey–understorey mismatch, we estimate that wildflower spring carbon budgets in the northeastern United States were 12–26% larger during Thoreau's era and project a 10–48% reduction during this century. This underappreciated phenomenon may have already reduced wildflower fitness and could lead to future population declines in these ecologically important species.

Drivers of vegetative dormancy across herbaceous perennial plant species - Richard P. Shefferson; Tiiu Kull; Michael J. Hutchings; Marc‐André Selosse; Hans Jacquemyn; Kimberly M. Kellett; Eric S. Menges; Richard B. Primack; Juha Tuomi; Kirsi Alahuhta; Sonja Hurskainen; Helen M. Alexander; et al. (Ecology Letters, 2018)
Vegetative dormancy, that is the temporary absence of aboveground growth for ≥ 1 year, is paradoxical, because plants cannot photosynthesise or flower during dormant periods. We test ecological and evolutionary hypotheses for its widespread persistence. We show that dormancy has evolved numerous times. Most species displaying dormancy exhibit life‐history costs of sprouting, and of dormancy. Short‐lived and mycoheterotrophic species have higher proportions of dormant plants than long‐lived species and species with other nutritional modes. Foliage loss is associated with higher future dormancy levels, suggesting that carbon limitation promotes dormancy. Maximum dormancy duration is shorter under higher precipitation and at higher latitudes, the latter suggesting an important role for competition or herbivory. Study length affects estimates of some demographic parameters. Our results identify life historical and environmental drivers of dormancy. We also highlight the evolutionary importance of the little understood costs of sprouting and growth, latitudinal stress gradients and mixed nutritional modes.

Humidity does not appear to trigger leaf out in woody plants - Lucy Zipf; Richard B. Primack (International Journal of Biometeorology, 2017)

Extreme passive acoustic telemetry detection variability on a mesophotic coral reef, United States Virgin Islands - Jonathan Jossart; Richard S. Nemeth; Avram Primack; Robert Stolz (Marine Biology, 2017)

Past, present, and future land use of an iconic cape cod landscape - Richard B. Primack (Ecology, 2017)

Cranberry flowering times and climate change in southern Massachusetts - Elizabeth R. Ellwood; Susan R. Playfair; Caroline A. Polgar; Richard B. Primack (International Journal of Biometeorology, 2014)

Tree leaf out response to temperature: comparing field observations, remote sensing, and a warming experiment - Caroline A. Polgar; Richard B. Primack; Jeffrey S. Dukes; Crystal Schaaf; Zhuosen Wang; Susanne S. Hoeppner (International Journal of Biometeorology, 2014)

Modeling daily flowering probabilities: expected impact of climate change on Japanese cherry phenology - Jenica M. Allen; Maria A. Terres; Toshio Katsuki; Kojiro Iwamoto; Hiromi Kobori; Hiroyoshi Higuchi; Richard B. Primack; Adam M. Wilson; Alan Gelfand; John A. Silander (Global Change Biology, 2014)
Understanding the drivers of phenological events is vital for forecasting species’ responses to climate change. We developed flexible Bayesian survival regression models to assess a 29‐year, individual‐level time series of flowering phenology from four taxa of Japanese cherry trees ( Prunus spachiana , Prunus × yedoensis , Prunus jamasakura , and Prunus lannesiana) , from the Tama Forest Cherry Preservation Garden in Hachioji, Japan. Our modeling framework used time‐varying (chill and heat units) and time‐invariant (slope, aspect, and elevation) factors. We found limited differences among taxa in sensitivity to chill, but earlier flowering taxa, such as P. spachiana , were more sensitive to heat than later flowering taxa, such as P. lannesiana . Using an ensemble of three downscaled regional climate models under the A1B emissions scenario, we projected shifts in flowering timing by 2100. Projections suggest that each taxa will flower about 30 days earlier on average by 2100 with 2–6 days greater uncertainty around the species mean flowering date. Dramatic shifts in the flowering times of cherry trees may have implications for economically important cultural festivals in Japan and East Asia. The survival models used here provide a mechanistic modeling approach and are broadly applicable to any time‐to‐event phenological data, such as plant leafing, bird arrival time, and insect emergence. The ability to explicitly quantify uncertainty, examine phenological responses on a fine time scale, and incorporate conditions leading up to an event may provide future insight into phenologically driven changes in carbon balance and ecological mismatches of plants and pollinators in natural populations and horticultural crops.

Disentangling the paradox of insect phenology: are temporal trends reflecting the response to warming? - Elizabeth R. Ellwood; Jeffrey M. Diez; Inés Ibáñez; Richard B. Primack; Hiromi Kobori; Hiroyoshi Higuchi; John A. Silander (Oecologia, 2012)

Bird migration times, climate change, and changing population sizes - ABRAHAM J. MILLER‐RUSHING; TREVOR L. LLOYD‐EVANS; RICHARD B. PRIMACK; PAUL SATZINGER (Global Change Biology, 2008)
Past studies of bird migration times have shown great variation in migratory responses to climate change. We used 33 years of bird capture data (1970–2002) from Manomet, Massachusetts to examine variation in spring migration times for 32 species of North American passerines. We found that changes in first arrival dates – the unit of observation used in most studies of bird migration times – often differ dramatically from changes in the mean arrival date of the migration cohort as a whole. In our study, the earliest recorded springtime arrival date for each species occurred 0.20 days later each decade. In contrast, the mean arrival dates for birds of each species occurred 0.78 days earlier each decade. The difference in the two trends was largely explained by declining migration cohort sizes, a factor not examined in many previous studies. We found that changes in migration cohort or population sizes may account for a substantial amount of the variation in previously documented changes in migration times. After controlling for changes in migration cohort size, we found that climate variables, migration distance, and date of migration explained portions of the variation in migratory changes over time. In particular, short‐distance migrants appeared to respond to changes in temperature, while mid‐distance migrants responded particularly strongly to changes in the Southern Oscillation Index. The migration times of long‐distance migrants tended not to change over time. Our findings suggest that previously reported changes in migration times may need to be reinterpreted to incorporate changes in migration cohort sizes.

Evaluating Conservation Biology Textbooks - Richard B. Primack (Conservation Biology, 2003)

Response - Richard B. Primack (Conservation Biology, 2001)

Publish Again in Another Language - Richard B. Primack (Conservation Biology, 2001)

Publish Again in Another Language - Richard B. Primack (Conservation Biology, 2001)

Reply to Rejmánek, 'On the use and Misuse of Transition Matrices in Plant Population Biology' - Brian Drayton; Richard B. Primack (Biological Invasions, 2000)

Dragonfly Pond Restoration Promotes Conservation Awareness in Japan - Richard Primack; Hiromi Kobori; Seiwa Mori (Conservation Biology, 2000)

Experimental Extinction of Garlic Mustard (Alliaria petiolata) Populations: Implications for Weed Science and Conservation Biology - Brian Drayton; Richard B. Primack (Biological Invasions, 1999)

Evolutionary change in seed size among some legume species: The effects of phylogeny - Hyesoon Kang; Richard B. Primack (Plant Systematics and Evolution, 1999)